Il-6 Serum Levels and Production Is Related to an Altered Immune Response in Polycystic Ovary Syndrome Girls with Insulin Resistance. (15th February 2011) - Fulghesu, Anna M.; Sanna, Francesca; Uda, Sabrina; Magnini, Roberta; Portoghese, Elaine; Batetta, Barbara
Abstract : Polycystic ovarian syndrome (PCOS) is frequently characterized by obesity and metabolic diseases including hypertension, insulin resistance, and diabetes in adulthood, all leading to an increased risk of atherosclerosis. The present study aimed to evaluate serum and production of inflammatory markers in adolescent Sardinian PCOS. On the basis of HOMA findings, patients were divided into noninsulin resistant (NIR) and insulin resistant (IR), and were weight- and age-matched with healthy girls. Inflammatory cytokines (TNF- α, IL-6, Il-10, TGF- β ) and lipokines (leptin, adiponectin), the reactant hs-CRP, and in vitro inflammatory lympho-monocyte response to microbial stimulus were evaluated. In healthy and PCOS subjects, leptin and hs-CRP were correlated with BMI, whereas adiponectin was significantly reduced in all PCOS groups. Although cytokines were similar in all groups, Interleukin-6 (IL-6) was significantly higher in IR PCOS. Moreover, in the latter group lipopolysaccharide-activated monocytes secreted significantly higher levels of IL-6 compared to NIR and control subjects. To conclude, IR PCOS displayed increased IL-6 serum levels and higher secretion in LPS-activated monocytes, whilst revealing no differences for other inflammatory cytokines. These results suggest that in PCOS patients an altered immune response to inflammatory stimuli is present in IR, likely contributing towards determining onset of a low grade inflammation.